PEMBUATAN PROGRAM APLIKASI SISTEM INFORMASI PARIWISATA KETEP PASS PADA KABUPATEN MAGELANG BERBASIS WEB - Rachel Noveris Sukisman; Ery Dewayani; Wasino Wasino (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Ketep Pass Tourism Information System On Magelang Regency Web Based developed with the purpose to promote Ketep Pass tourist attraction as online to Indonesia’s society widely. Ketep Pass Tourism Information System was made by using PHP Programming Language and MySQL. The results achieved from tourism information system is provide convenience to the management in managing the report that found in Login, Member, Comment, Ticket Sales, Facility, Ticket Price, Gallery, Employee, Position, Year of Position, Event Category, Events, News Category, News, Picture of News, & Admin module, and provide need information about Ketep Pass tourist attraction to web user that found in Home, About Us, Gallery, Facility, Information, Blog, Login, Sign Up, & My Account module. The methodology used in the making of this system is System Development Life Cycle (SDLC), which is containing planning, analysis, design, implementation, and maintenance phases.